Preventing Cauliflower Ear. (July 2020) - Gooch, Michael D.
Abstract : Traumatic auricular hematomas may be encountered in emergency care settings due to blunt trauma such as assaults or contact sports. Emergency nurse practitioners should be able to recognize and treat this injury to prevent complications. Treatment usually consists of evacuation of the hematoma by aspiration or incision and drainage using local or regional anesthesia, followed by the application of a pressure dressing or suturing. Without proper evacuation and steps to prevent reaccumulation, tissue necrosis and deformity (i.e., cauliflower ear) may occur.